Comparison of deep transfer learning models for cancer diagnosis - Joya, Nadia Islam; Turna, Tasfia Haque; Sukhi, Zinia Nawrin; Promy, Tania Ferdousey (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.